Role of Product Quality and Price on Purchase Decision of Goox Products - Fahrizal Azhar; Uli Wildan Nuryanto; Abdul Rasyid; Markus Asta Patma Nugraha; Sutrisno (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study was to determine and analyze the effect of product quality on purchasing decision, to determine and analyze the effect of price on purchase decisions and to determine and analyze the effect of product quality and price on purchasing decisions for goox shoes. The approach used in this study is an associative approach. The population in this study is the whole. While the sample that meets the criteria for sampling the observations made amounted to 100 respondents. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t-test and F-test), and the Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. Partially it is known that product quality has a positive and significant influence on purchasing decisions for goox shoes where it is obtained (t-count.6, 692) > (t-table 1,984) and sig 0.000 < 0.05. Partially it is known that the price has a positive and significant influence on the decision to buy goox shoes where it is obtained (t-count.4.453) > (t-table 1.984) and the sig. 0.000 < 0.05. Simultaneously, it is known that product quality and price have a significant influence on the decision to buy goox shoes where it is obtained (F-count.37.694) > (F-table 3.09) and sig 0.000 <0.05.